Analysing regional unemployment rates, GDP per capita and financial support for regional suicide prevention programme on suicide mortality in Japan using governmental statistical data. Issue 8 (27th August 2020) - Okada, Motohiro; Hasegawa, Toshiki; Kato, Ryo; Shiroyama, Takashi
Abstract : Objectives: To explore the mechanisms of reduced suicide mortality in Japan, which decreased from 25.7 to 16.5 per 100 000 people following the comprehensive suicide prevention programme from 2009 to 2018, the present study determined the relationship between regional suicide mortality, socioeconomic data (GDP per capita, unemployment rates) and financial support for regional suicide prevention programmes. Design and setting: Stepwise multiple regression analysis was used to determine the effects of regional GDP per capita, unemployment rates and implementation amount of financial support for regional suicide prevention programmes (Emergency Fund to Enhance Community-Based Suicide Countermeasures—EFECBSC) on age and gender disaggregated suicide mortalities in Japan between 2009 and 2018. Data on each prefecture's complete unemployment rates, GDP per capita and implementation amount of EFECBSC sub-divisions were derived from an official Japanese governmental database. Results: Both prefectural enlightenment and intervention model programmes were found to lead to a decrease in male suicide mortality, but were less effective in reducing female suicide mortality. Municipal enlightenment and intervention model programmes were also less effective in reducing suicide mortality. Municipal development programmes for listener and leader led to a greater decrease in suicide mortality for both men and women compared with such programmes at the prefectural level. Contrary to our expectations, reduced complete unemployment rate only reduced suicide mortality in the older male population without affecting female suicide mortality. Conclusion: The study findings suggest an inverse relationship between financial support and suicide mortality in Japan. Furthermore, independent factors in the reduction of suicide mortality rates provide important information for planning evidence-based and cost-effective regional suicide prevention programmes.